Animal health emergencies: a gender-based analysis for planning and policy - Carlin, Ellen; Standley, Claire E.; Hardy, Emily; Donachie, Daniel; Brand, Tianna; Greve, Lydia; Fevre, Sonia; Wenham, Clare (Frontiers in Veterinary Science, 2024)
There has been increasing recognition of gender-based inequity as a barrier to successful policy implementation. This consensus, coupled with an increasing frequency of emergencies in human and animal populations, including infectious disease events, has prompted policy makers to re-evaluate gender-sensitivity in emergency management planning. Seeking to identify key publications relating to gendered impacts and considerations across diverse stakeholders in different types of animal health emergencies, we conducted a non-exhaustive, targeted scoping review. We developed a matrix for both academic and policy literature that separated animal health emergencies into two major categories: humanitarian crises and infectious disease events. We then conducted semi-structured interviews with key animal health experts. We found minimal evidence of explicit gender responsive planning in animal health emergencies, whether humanitarian or infectious disease events. This was particularly salient in Global North literature and policy planning documents. Although there are some references to gender in policy documents pertaining to endemic outbreaks of African swine fever (ASF) in Uganda, most research remains gender blind. Despite this, implicit gendered themes emerged from the literature review and interviews as being direct or indirect considerations of some research, policy, and implementation efforts: representation; gendered exposure risks; economic impact; and unpaid care. Absent from both the literature and our conversations with experts were considerations of mental health, gender-based violence, and intersectional impacts. To remedy the gaps in gender-based considerations, we argue that the intentional inclusion of a gender transformative lens in animal health emergency planning is essential. This can be done in the following ways: 1) collection of disaggregated data (race, gender, sexual orientation, etc.); 2) inclusion of gender experts; and 3) inclusion of primary gendered impacts (minimal representation of women in policy positions, gender roles, economic and nutrition impacts) and secondary gendered impacts (gender-based violence, mental health, additional unpaid care responsibilities) in future planning.